Assessing the relationship between students’ learning styles and mathematics critical thinking ability in a ‘Cluster School’ / Salimah Ahmad ... [et al.] - Ahmad, Salimah; Abd Nassir, Asyura; Tarmuji, Nor Habibah; Yusob, Khairul Firhan; Yacob, Nor Azizah (2021)
Identifying students’ learning styles in class can help teachers plan a strategy for adapting the best teaching method to help them understand. The objective of this study is to identify the potential relationship between the students’ preferred learning style (visual, auditory and kinesthetic) and their critical thinking in mathematics. A set of questionnaires consisting of 14 questions and critical thinking problems were distributed to sixty-two 17-year-old students at a cluster secondary school in Pahang, Malaysia. The quantitative data collected were analyzed using descriptive statistics, Spearman’s Rank Correlation Coefficient, and ANOVA and t-test. The findings indicate that the most popular learning style is visual (71%), followed by auditory (22.6%) and kinesthetic (6.5%). Further, the preferred learning style and critical thinking are not significantly related. Based on this study, the teachers can identify their students’ learning style and make adjustment to provide various teaching methods consistent with the students’ learning style in the future. It is also will help the students to build self-confidence and plan their study strategy.